Effect of implant number and height on the biomechanics of full arch prosthesis - Tribst, João Paulo Mendes [UNESP]; de Oliveira Dal Piva, Amanda Maria [UNESP]; Borges, Alexandre Luiz Śouto [UNESP]; Bottino, Marco Antonio [UNESP] (Universidade Estadual de Campinas, 2018)
Aim: The goal of this study was to clarify the stress distribution in a full arch prosthesis according to the implant number and height in order to guide the clinical choice during planning. Methods: A computational analysis was performed to analyze the stress distribution in implants and bone tissue according to implant number (3,4 or 5) and height (5,8,11 mm). A model of a jaw with polyurethane properties to simulate bone tissue was created through the Rhinoceros software (version 5.0 SR8, McNeel North America, Seattle, WA, USA). The titanium bar was fixed to the implant through a retention screw. The final geometry was exported in STEP format to ANSYS (ANSYS 15.0, ANSYS Inc., Houston, USA) and all materials were considered homogeneous, isotropic and linearly elastic. To assess distribution of stress forces, an axial load (200 N) was applied on the cantilever. Results in Von-Mises stress and strain criteria's were obtained for implants and bone, respectively. Qualitative and quantitative evaluations were performed. Results: The implant number and height influenced the prosthesis biomechanics, with more von-Mises stress and bone strain concentration for combination of 3 implants with 5 mm. Conclusion: It was concluded that higer length and more quantity of implant supporting a full arch prosthesis promoted less stress concentration during the simulated load. Decreasing the number of implants in rehabilitation is more harmful than decreasing their length for the stress and strain distribution.
Keywords: Dental implants. Finite element analysis. Bone implant interface. Prosthodontics